PERBANDINGAN KOMPETENSI FISIKA SISWA MENGGUNAKAN BAHAN AJAR BERMUATAN KECERDASAN KOMPREHENSIF ANTARA PEMBELAJARAN MENGIMPLEMENTASIKAN MODEL PBL DAN INKUIRI DI KELAS X SMAN 4 PADANG - Annisa Rahma Sari; Djusmaini Djamas; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2016)
The using of learning material and to apply it in the learning model to support achievement of students’ competence in the Physics subject. The learning material existed recently only contain knowledge, so they have not supported the achievement of competence overally. The other side, the learning model was still teacher-centered which caused students’ low ability in thinking and solving problems. The aim of this research is to find out the difference of students’ Physics competence by applying the learning material contains comprehensive intelligence which are implemented in two learning models, PBL and Inquiry at grade X of SMAN 4 Padang. This was a Quasi Experiment research with the Randomize Group Only Design. Samples were taken using Purposive Sampling and obtained grade X MIA 5 as the experiment class 1 and grade X MIA 7 as the experiment class 2. The data of this research includes the competence of spiritual, social, knowledge and skills. The instruments are written test for competence of knowledge, observation sheets for competence of spiritual and social, and assessment scale completed by rubric for competence of skill. The technique of data analysis was using the equivalence test of two means in the tangible degree of 0,05. Based on the data analysis, it can be concluded that there are significant differences of students’ Physics competence by applying the learning material contains comprehensive intelligence implemented between two learning models; PBL and Inquiry at grade X of SMAN 4 Padang in two aspects; cognitive and psychomotor